The BMP inhibitor follistatin-like 1 (FSTL1) suppresses cervical carcinogenesis - Zhao, Chenjing; Chen, Zhongjie; Zhu, Li; Miao, Yunheng; Guo, Jiasen; Yuan, Zhiyong; Wang, Ping; Li, Lian; Ning, Wen (Frontiers in Oncology, 2023)
Follistatin-like 1 (FSTL1) is a cancer-related matricellular secretory protein with contradictory organ-specific roles. Its contribution to the pathogenesis of cervical carcinoma is still not clear. Meanwhile, it is necessary to identify novel candidate genes to understand cervical carcinoma's pathogenesis further and find potential therapeutic targets. We collected cervical carcinoma samples and matched adjacent tissues from patients with the locally-advanced disease and used cervical carcinoma cell lines HeLa and C33A to evaluate the effects of FSTL1 on CC cells. The mRNA transcription and protein expression of FSTL1 in cervical carcinoma tumor biopsy tissues were lower than those of matched adjacent tissues. Patients with a lower ratio of FSTL1 mRNA between the tumor and its matched adjacent tissues showed a correlation with the advanced cervical carcinoma FIGO stages. High expression of FSTL1 markedly inhibited the proliferation, motility, and invasion of HeLa and C33A. Regarding mechanism, FSTL1 plays its role by negatively regulating the BMP4/Smad1/5/9 signaling. Our study has demonstrated the tumor suppressor effect of FSTL1, and these findings suggested a potential therapeutic target and biomarker for cervical carcinoma.